Nail Psoriasis: An Updated Review of Currently Available Systemic Treatments - Battista T; Scalvenzi M; Martora F; Potestio L; Megna M (Dove Medical Press, 2023)
Teresa Battista, Massimiliano Scalvenzi,* Fabrizio Martora,* Luca Potestio, Matteo Megna Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Fabrizio Martora, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 81 - 7462457, Fax +39 - 81 - 7462442, Email fabriziomartora92@libero.itBackground: Nail psoriasis (NP) has a prevalence that ranges from 10 to 82% among patients with psoriasis (PsO) and is one of the most common difficult to treat site of psoriasis. We performed a thorough review of the literature, exploring evidence regarding all available NP systemic treatments, describing also in detail NP dedicated clinical trials.Methods: A literature search was conducted in PubMed and Embase prior to February 2023 using a combination of the terms "nail" AND "psoriasis" AND "systemic therapy" AND/OR "systemic treatment". A total of 47 original studies and case reports were reviewed in this article.Results: Systemic therapies should be considered when the disorder involves more than 3 nails, has extensive skin and joint involvement, and has a significant impact on QoL, due to their best long-term efficacy. In detail, conventional and biologic systemic drugs demonstrated efficacy in recent trials, including acitretin, methotrexate, cyclosporine, apremilast, adalimumab, infliximab, etanercept, certolizumab, golimumab, ustekinumab, secukinumab, ixekizumab, brodalumab, bimekizumab, guselkumab, risankizumab and tildrakizumab.Conclusion: Several therapies have demonstrated efficacy and safety in the treatment of NP; however, the choice of treatment depends not only on the severity of the nail involvement, but also on whether PsA is present, the patient's comorbidities other than PsA, previous treatment history, and the patient's drug preferences.Keywords: nail psoriasis, psoriasis, treatment, biologics